ANALISIS DAMPAK PERILAKU FEAR OF MISSING OUT (FOMO) TERHADAP PENGGUNAAN MEDIA SOSIAL - Dewi Shinta; Marniati Marniati; Herawati Herawati (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2025)
Fear of Missing Out (FoMO) is a phenomenon of the fear of being left out or missing important information, often occurring due to social media. This study aims to analyze the impact of Fear of Missing Out (FoMO) behavior on social media usage. The method used in this study is a literature review. The results of this literature review indicate that there are 14 variables positively correlated with FoMO: social comparison, social media addiction, loneliness, perfectionism, stalking, social media fatigue, academic stress, need for affiliation, neuroticism, anxiety, depression, stress, relative deprivation, and self-regulatory fatigue. Three variables negatively correlated with FoMO are psychological well-being, self-regulation, and self-control.